Memristors get the hues - Sarwat, SG; Bhaskaran, H (Springer Nature, 2021)
The memristor, in which an external electric field controls the formation and annihilation of conductive channels, has been described both as a missing electronic element and a memory and computational element. Here, their utility as building blocks for promising reflective and energy-efficient colour technology is described.